On what god would do - Lovering, Rob (International journal for philosophy of religion, 2009)
Many debates in the philosophy of religion, particularly arguments for and against the existence of God, depend on a claim or set of claims about what God—qua sovereign, omnipotent, omniscient, and perfectly good being—would do, either directly or indirectly, in particular cases or in general. Accordingly, before these debates can be resolved we must first settle the more fundamental issue of whether we can know, or at least have justified belief about, what God would do. In this paper, I lay out the possible positions on the issue of whether we can know what God would do, positions I refer to as Broad Skeptical Theism, Broad Epistemic Theism, and Narrow Skeptical Theism. I then examine the implications of each of these views and argue that each presents serious problems for theism.